Esporte eletrônico : videogame como trabalho imaterial - Bernardino, Paulo Vitor Marques (2017)
E-sports are a professional video-game competition, virtual or presential, where the players compte between themselves for a award or a prize in cash. Its origns comes from information and communication high technology, in wich converges video-games, sports, jobs and leisure. Economic, social, cultural and emotional relationships are started in its ecosysthem. From this aspect, we establish its aim to undrstand in wich ways the video-game, in this challengeable environment is appropriate to the immaterial labour world, and based on this research we are able to discribe the brazilian e-Sports environment. The metodology used on this research is the netnography and we selected three competitive games, The League of Legends, Dota 2 and Hearthstone and all their respective virtual communities as database. We formulated and lauched two virtual opened quiz, to proffesionals and fans of e-Sports. As a result, we indentified the brazilian e-Sports environment is in full development and professionalization process. The immaterial production of ideas and relationships turns a game into a show, a social bond vector and a raw material configured those contents as entertainment.